Implementing Kurikulum Merdeka (The Independent Curriculum) in the teaching of English in Indonesia: a critical literature review - M. Zaenal Abidin; Malisa Malisa (IRecall Journal, 2024)
Numerous of recent studies indicate strong improvement of the implementation of Kurikulum Merdeka (The independent curriculum), primarily by showing numerical data and claiming that it was relevant to the globalized world, and it has improved. However, few researchers potraying the different results to different areas to English Language Teaching (ELT). This study is meant to fill this gap and address the representation of English outcomes through documentation as well as to figure out the process of its implementation. It focuses on theories, curriculum, implementations, and results in ELT. This research is literature study research. The analysis results are then used to know (1) representation of different results in the English language (2) Knowing the implementation process of the independent curriculum in ELT. The results showed that numerous distinct outcomes of the independent curriculum mostly happen in less representative area either in western or eastern Indonesia. Further, the implementations of the independent curriculum indicate strong revitalization need to the student and schools. As the conclusion, the implementations of the independent curriculum sparked the teachers’ readiness as well as revitalization based on students’ need before implementing the independent curriculum.